Integrated planning and scheduling for precast concrete production - Zhai, Xiaofeng (2008)
In the research, an integrated planning and scheduling model, IPSMPP, is established for make-to-order precast production using a comprehensive casting organization. IPSMPP covers both aggregate planning at the tactical level and detailed scheduling at the operational level. Five modules at the two levels are designed for different planning purposes. A Simulation-GA based approach is proposed to solve specific problems in every module. Specialized priority rules and bidirectional simulation passes are further formulated in order to improve the schedule performance. Based on the model and its inner workings, a prototype system has been developed for model validation. Finally, two tests are conducted for aggregate planning and detailed scheduling respectively. The validity of IPSMPP has been demonstrated by comparison of the results from the prototype system, planning methods used in practice, and other traditional approaches. IPSMPP can considerably reduce not only the total variable cost, but also cost in nearly every cost category, thus leading to feasible schedules with best performance. In conclusion, the main contributions made in this research lies in the following aspects.